1999
DOI: 10.1002/(sici)1097-4679(199901)55:1<79::aid-jclp8>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Adult and geriatric normative data and validation of the profile of mood states

Abstract: The Profile of Mood States (POMS; McNair, Lorr, & Droppleman) is widely used to assess mood states. However, the utility of the POMS has been restricted by the lack of normative data from the general population. We report on our adult (N = 400) and geriatric (N = 170) POMS standardization samples. Both groups were age-, gender-, and race-stratified according to 1990 census data. We also report on convergent and discriminant validity of POMS scales, using a multitrait, multimethod paradigm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
218
6
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(230 citation statements)
references
References 14 publications
4
218
6
2
Order By: Relevance
“…It has been also validated for use in a nonpsychiatric population including general population, college students and medical students [11][12][13]. Nyenhuis et al reported a mean BDI score of 6.8 ± 5.5 for general population [13].…”
Section: Discussionmentioning
confidence: 99%
“…It has been also validated for use in a nonpsychiatric population including general population, college students and medical students [11][12][13]. Nyenhuis et al reported a mean BDI score of 6.8 ± 5.5 for general population [13].…”
Section: Discussionmentioning
confidence: 99%
“…Cronbach alpha was .60 in the current study. Construct validity of the POMS was established in a racially diverse sample of 594 U.S. adults (Nyenhuis, Yamamoto, Luchetta, Terrien, & Parmentier, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that standard deviations > 1.5 above the mean could be used as a cut-off point between clinical and non-clinical scores, to be consistent with the international use of other psychological measures [18]. For this sample, it may be prudent to refer scores of > 17 to a psychologist for a further investigation, or at least clarification.…”
Section: Objective 2: Value Of Entry Stpi Scores To Predict Qualificamentioning
confidence: 99%